Are Small Reimbursement Changes Enough to Change Cancer Care? Reimbursement Variation in Prostate Cancer Treatment - Ellis, Shellie D. (J Oncol Pract, 2016)
PURPOSE: The Centers for Medicare and Medicaid Services recently initiated small reimbursement adjustments to improve the value of care delivered under fee-for-service. To estimate the degree to which reimbursement influences physician decision making, we examined utilization of gonadotropin-releasing hormone (GnRH) agonists among urologists as Part B drug reimbursement varied in a fee-for-service environment. METHODS: We analyzed treatment patterns of urologists treating 15,128 men included in SEER-linked Medicare claims who were diagnosed with localized prostate cancer between January 1, 2000, and December 31, 2003. We calculated a reimbursement generosity index to measure differences in GnRH agonist reimbursement among regional Medicare carriers and over time. We used multilevel analysis to control for patient and provider characteristics. RESULTS: Among urologists treating early-stage and lower grade prostate cancer, variation in reimbursement was not associated with overuse of GnRH agonists from 2000 to 2003, a period of guideline stability (odds ratio, 1.00; 95% CI, 0.99 to 1.00). CONCLUSION: Small differences in androgen-deprivation therapy reimbursement generosity were not associated with differential use. Fee-for-service reimbursement changes currently being implemented to improve quality in fee-for-service Medicare may not affect patterns of cancer care.